Formulation of chitosan–TPP–pDNA nanocapsules for gene therapy applications - Gaspar, Vítor Manuel Abreu (2018)
The encapsulation of DNA inside nanoparticles meant for gene delivery applications is a challenging process where several parameters need to be modulated in order to design nanocapsules with specific tailored characteristics. The purpose of this study was to investigate and improve the formulation parameters of plasmid DNA (pDNA) loaded in chitosan nanocapsules using tripolyphosphate (TPP) as polyanionic crosslinker. Nanocapsule morphology and encapsulation efficiency were analyzed as a function of chitosan degree of deacetylation and chitosan–TPP ratio. The manipulation of these parameters influenced not only the particle size but also the encapsulation and release of pDNA. Consequently the transfection efficiency of the nanoparticulated systems was also enhanced with the optimization of the particle characteristics. Overall, the differently formulated nanoparticulated systems possess singular properties that can be employed according to the desired gene delivery application.